I giovani italiani, la ‘non politica’ e nuovi cleavages - Pirni, Andrea (SocietàMutamentoPolitica, 2012)
The article aims to show two dynamics, deeply connected, leading to the ‘non-politics’ among new generations: the political individualization and the privatization of public sphere. Then these dynamics are linked with the present Italian context to focalize new cleavages between young people and politics, society and main culture. Finally some scenarios will be draw up from the current socio-political change.